A New Approach to the Solution of Non-Linear Integral Equations via Various FBe-Contractions - Sumati Kumari Panda (Symmetry, 2019)
In this article, we introduce and establish various approaches related to the F-contraction using new sorts of contractions, namely the extended <semantics> F B e </semantics> -contraction, the extended <semantics> F B e </semantics> -expanding contraction, and the extended generalized <semantics> F B e </semantics> -contraction. Thereafter, we propose a simple and efficient solution for non-linear integral equations using the fixed point technique in the setting of a <semantics> B e </semantics> -metric space. Moreover, to address conceptual depth within this approach, we supply illustrative examples where necessary.